Rhizosphere bacteria help plants tolerate abiotic stress - Yang, Jungwook; Kloepper, Joseph W.; Ryu, Choong-Min (Trends in plant science, 2009)
Plant-growth-promoting rhizobacteria (PGPR) are associated with plant roots and augment plant productivity and immunity; however, recent work by several groups shows that PGPR also elicit so-called ‘induced systemic tolerance’ to salt and drought. As we discuss here, PGPR might also increase nutrient uptake from soils, thus reducing the need for fertilizers and preventing the accumulation of nitrates and phosphates in agricultural soils. A reduction in fertilizer use would lessen the effects of water contamination from fertilizer run-off and lead to savings for farmers.